2012
DOI: 10.1159/000336335
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for the Inducible Proteasomal Subunits LMP7 and MECL1 in Cytokine Production by Activated Murine Splenocytes

Abstract: Background and Purpose: The proteasome is a multi-subunit complex that proteolytically cleaves proteins. The replacement of the constitutive proteasome subunits β1, β2, and/or β5 with the IFNγ-inducible subunits LMP2, MECL1, and/or LMP7 results in the ‘immunoproteasome’. The inducible subunits change the cleavage specificities of the proteasome, but it is unclear whether they have functions in addition to this. The purpose of the present study was to determine the role of the proteasome in general, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…Collectively, these results underscore the importance of LMP subunits in the proteasome of macrophages and splenocytes [27]. We have established that different proteasome proteases regulate levels of cytokine gene expression and protein expression differentially.…”
Section: 3 the Pivotal Role Of Proteasome Proteases In Modulating Lmentioning
confidence: 67%
See 2 more Smart Citations
“…Collectively, these results underscore the importance of LMP subunits in the proteasome of macrophages and splenocytes [27]. We have established that different proteasome proteases regulate levels of cytokine gene expression and protein expression differentially.…”
Section: 3 the Pivotal Role Of Proteasome Proteases In Modulating Lmentioning
confidence: 67%
“…Since LPS does not directly activate CD4+ T cells, we used phorbol-12-myristate-13-acetate (PMA)/ionomycin as an agonist, thus bypassing the receptor. LMP7/LMP10-null splenocytes exhibited reduced levels of gene expression of IL-10, IL-4, IFN-γ, IL-2Rβ t-bet and GATA-3 (transcription factors) in response to agonists, whereas, induction of IL-13, IL-2, TNF-α and IL-2Rα was essentially normal in these knockout mice as compared to wild-type mice, and were found to be LMP-independent [27] and may therefore be X, Y, Z- dependent. Lactacystin (which predominantly inhibits the chymotrypsin-like activity of the proteasome) pretreatment of LMP7/LMP10-null splenocytes, followed by PMA/ionomycin, reduces gene expression of IL-2, IFN-γ IL-4, IL-13, TNF-α(cytokines), IL-2Rα and IL-2Rβ (receptors) t-bet and GATA-3 (transcription factors).…”
Section: 3 the Pivotal Role Of Proteasome Proteases In Modulating Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the Immunoproteasome plays a role in cytokine production in response to inflammation or infection, and cells or animals deficient in Immunoproteasome subunits have decreased cytokine signaling (Muchamuel et al, 2009, Arima et al, 2011, Kitamura et al, 2011, Liu et al, 2012, Rockwell et al, 2012). Cytokines that have been shown to be regulated by the Immunoproteasome include interferon- γ, IL-2, IL-4, IL-10, and IL-23, and cells from LMP7 −/− MECL1 −/− knockout mice have been used to show that lack of the Immunoproteasome also causes decreased expression of two cytokine transcription factors, GATA3 and t-bet (Rockwell et al, 2012, Muchamuel et al, 2009).…”
Section: The Immunoproteasome In Antigen Presentation and Infectionsmentioning
confidence: 99%
“…Cytokines that have been shown to be regulated by the Immunoproteasome include interferon- γ, IL-2, IL-4, IL-10, and IL-23, and cells from LMP7 −/− MECL1 −/− knockout mice have been used to show that lack of the Immunoproteasome also causes decreased expression of two cytokine transcription factors, GATA3 and t-bet (Rockwell et al, 2012, Muchamuel et al, 2009). Taken together, these findings suggest that the Immunoproteasome not only plays a role in responding to inflammation, but also participates in activating the inflammatory cytokines, as well.…”
Section: The Immunoproteasome In Antigen Presentation and Infectionsmentioning
confidence: 99%